Do Oil Price Shocks Matter for Competition: A Vector Error Correction Approach to Russian Labor Market - Kurnysheva, Irina; Burakov, Dmitry (International Journal of Energy Economics and Policy, 2017)
In this article we test the hypothesis about the impact of oil prices shocks on the competition in the labor market on the example of oil-exporting country. According to the hypothesis of the study, positive (negative) oil price shock leads to an increase (fall) in the demand for labor, which, in turn, leads to growth (slowdown in growth) of wages adjusted for inflation given wages inelasticity in the short term. Based on data for 1990-2016 we study a case of Russia, using vector error correction model. In the result we come to conclusion that a positive oil price shock leads to an increase of the aggregate level of wages in the economy and employment growth. A negative oil price shock leads to a slowdown in the growth of the aggregate level of wages and to an increase in the average level of unemployment. Keywords: oil prices, employment, competition, labor, human capital. JEL Classifications: Q41, E24, F16, C12